Paleoethnobotany of the archaeological site of Qhenchapata, ayllu sucso Auccaylle (San Sebastián - Cuzco) - Fernández Palomino, Mildred (2021)
In this work we present the recorded paleoethnobotany at the site of Qhenchapata, located in San Sebastián district, Cusco region, where we find two occupations determined for two fires: the first, when finished the Late Horizon or Inca Period; and the second one, in the Colonial Period. The paleoethnobotany evidence plus archaeology evidence recovered during the excavation process determined what was the use of the architecture present in this place.